A Study on Arch Length Among Dentoalveolar Class I, Class II and Class III Malocclusion of Bangladeshi Population - Biswas, Ashis Kumar; Hassan, Gazi Shamim; Akhter, Nasreen; Ghosh, Ranjit; Babu, Mohammad Rakibul Islam (City Dental College Journal, 2012)
Objectives : To study the variations in arch length among different classes of dento-alveolar malocclusion in the permanent dentition. Materials and Methods: Both male and female Bangladeshi subjects with permanent dentition who attended during 1st July 2007 to 1st January 2011 to the Department of Orthodontics, BSMMU for treatment were included in this study. Dental arch length were measured from dental casts of the permanent dentition of 96 Bangladeshi subjects of which 48 male, 48 female, 24 class 1, 24 class 2 div. I, 24 class 2 div. II, 24 class III. Arch length was measured by adapting a length of brass wire (diameter 0.5 mm) on the maxillary and mandibular arches. Comparison of arch length was done among different malocclusion classes. Results: In these study we found maxillary arch length was largest in class II div. 1 malocclusion. Mandibular arch length was highest in class III and lowest in class II div. 1 malocclusion. Least significant difference (LSD) is used to compare two of the four group. P<0.05 was set as the level of significance. Conclusions : Class III malocclusion has large lower arch and short upper arch. In Class II division 1, arch length is larger in upper than lower arch and Class II division 2 show the shortest maxillary arch length. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11827 City Dental College Journal Vol.9(1) 2012 1-3